A multicenter, randomized comparison between 2, 5, and 8 mg of perineural dexamethasone for ultrasound-guided infraclavicular block. (3rd January 2019) - Bravo, Daniela; Aliste, Julian; Layera, Sebastián; Fernández, Diego; Leurcharusmee, Prangmalee; Samerchua, Artid; Tangjitbampenbun, Amornrat; Watanitanon, Arraya; Arnuntasupakul, Vanlapa; Tunprasit, Choosak; Gordon, Aida; Finlayson, Roderick J; et al.
Abstract : Background and objectives: This multicenter, randomized trial compared 2, 5, and 8 mg of perineural dexamethasone for ultrasound-guided infraclavicular brachial plexus block. Our research hypothesis was that all three doses of dexamethasone would result in equivalent durations of motor block (equivalence margin=3.0 hours). Methods: Three hundred and sixty patients undergoing upper limb surgery with ultrasound-guided infraclavicular block were randomly allocated to receive 2, 5, or 8 mg of preservative-free perineural dexamethasone. The local anesthetic agent (35 mL of lidocaine 1%-bupivacaine 0.25% with epinephrine 5 µg/mL) was identical in all subjects. Patients and operators were blinded to the dose of dexamethasone. During the performance of the block, the performance time, number of needle passes, procedural pain, and complications (vascular puncture, paresthesia) were recorded. Subsequently a blinded observer assessed the success rate (defined as a minimal sensorimotor composite score of 14 out of 16 points at 30 min), onset time as well as the incidence of surgical anesthesia (defined as the ability to complete surgery without local infiltration, supplemental blocks, intravenous opioids, or general anesthesia). Postoperatively, the blinded observer contacted patients with successful blocks to inquire about the duration of motor block, sensory block, and postoperative analgesia. The main outcome variable was the duration of motor block. Results: No intergroup differences were observed in terms of technical execution (performance time/number of needle passes/procedural pain complications), onset time, success rate, and surgical anesthesia. Furthermore, all three doses of dexamethasone provided similar durations of motor block (14.9–16.1 hours) and sensory block. Although 5 mg provided a longer analgesic duration than 2 mg, the difference (2.7 hours) fell within our pre-established equivalence margin (3.0 hours). Conclusions: 2, 5, and 8 mg of dexamethasone provide clinically equivalent sensorimotor and analgesic durations for ultrasound-guided infraclavicular block. Further trials are required to compare low (ie, 2 mg) and ultra-low (eg, 0.5–1 mg) doses of perineural dexamethasone for brachial plexus blocks. Trial registration number: TCTR20150624001.